America's First Great Moderation. (24th November 2017) - Davis, Joseph; Weidenmier, Marc D.
Abstract : We identify the longest expansion in U.S. history, a recession-free 16-year period from 1841 to 1856 that we call America's First Great Moderation. Using newer data on industrial production, we show that the record-long expansion was primarily driven by a boom in transportation-goods investment following the discovery of gold in California. Furthermore, the low volatility of industrial production and stock returns during the First Great Moderation, which occurred during a period without a U.S. central bank, is similar to that observed for the Second Great Moderation (1984–2007).